Alteration of Coding Properties of Polysome-Associated Messenger RNA in Potato Tuber Slices during Aging - Ishizuka, Masakatsu (1981)
Kinetics of polysome formation, translational capacity, and coding properties of polysome-associated messenger RNA were investigated in potato tuber tissue discs during aging. Polysome content rapidly increased immediately after slicing from 14% of total ribosomes in freshly sliced discs to 55% within 12 hours of aging. The amount of polysomal RNA also increased 5-fold during this period. Translational capacity of polysome-associated messenger RNA increased in parallel with the increase in content of polysomal RNA of the tissue discs when measured in a wheat germ cell-free system. Analysis of the in vitro translation products by sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed that the majority of polypeptides coded by the messenger RNA did not vary greatly during the period of rapid polysome formation. Three types of messenger RNA were found to change in amount during that period: those which appeared only after aging, those which disappeared during aging, and those which disappeared early but reappeared later in the aging period.